Jacobsen's syndrome: case report - L. Yu. Barycheva; L. I. Bachieva; N. A. Koz'mova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Introduction. Jacobsen syndrome (JS) is a rare genetic disease associated with the deletion of chromosome 11q, characterized by multiple malformations, hematological and immune disorders. The development of immunodeficiency in JS is often underestimated, which leads to recurrent infectious complications.   Presentation of a clinical case. The article presents a clinical case of a patient with a deletion of chromosome 11q and combined immunodeficiency. Our patient had recurrent infections, cytopenic syndrome, combined immunodeficiency, as well as other clinical manifestations of Jacobsen syndrome. In addition to a decrease in serum immunoglobulins, a deep deficiency of the T-cell link of immunity with a low content of T-lymphocytes, recent emigrants from the thymus, has been established.   Conclusions. The peculiarity of the presented clinical case is that with a relatively small amount of deletion 11q, the child realized a complete clinical phenotype of the disease and a deep combined immunodeficiency. The article was written to improve doctors' knowledge about this rare form of congenital immunodeficiency.